#### Answer

(x + 2)(x - 2)

#### Work Step by Step

$x^{2} - 4$
Compare the given expression with the generalized form:
$a^{2} - b^{2}$ = (a + b)(a - b).
Here, a=x and b = 2.
Thus,
$x^{2} - 4$ = (x + 2)(x - 2).

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

(x + 2)(x - 2)

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.